Peran Keunggulan Bersaing Dalam Memediasi Orientasi Pasar, Orientasi Kewirausahaan Terhadap Kinerja Pemasaran (Study Pada Pengolah Dan Pemasar Hasil Perikanan Kabupaten Wakatobi) - La Ode Agusrianto; Adnan Hakim; Hayat Yusuf; Valentinus Amstrong (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to examine and explain the role of competitive advantage in mediating market orientation, entrepreneurial orientation on marketing performance (a study on the fishery product processing and marketer in Wakatobi Regency). The population of this research is a group of fishery product processors and marketers in Wakatobi Regency, totaling 540 people, the number of samples being 55 people. The data from the sample/respondent were analyzed using SmartPLS in order to obtain the results of the causal relationship between the variables developed in the model. The results of testing the role of competitive advantage in mediating market orientation, entrepreneurial orientation on marketing performance (a study on the processing and marketing of fishery products in Wakatobi Regency), are as follows; the effect of market orientation on competitive advantage has a path coefficient of 0.518 with a probability level of 0.000 (p<0.05), the effect of market orientation on marketing performance has a path coefficient of 0.276 with a probability level of 0.020 (p<0.05), the influence of entrepreneurship to competitive advantage has a path coefficient of 0.384 with a probability level of 0.002 (p < 0.05), the influence of entrepreneurial orientation on marketing performance has a path coefficient of 0.218 with a probability level of 0.076 (p < 0.05), the effect of competitive advantage on marketing performance has a path coefficient of 0.487 with a probability level of 0.000 (p < 0.05), the effect of market orientation on marketing performance through competitive advantage has a path coefficient of 0252 with a probability level of 0.001 (p<0.05), the influence of entrepreneurial orientation on marketing performance through competitive advantage ng has a path coefficient of 0.187 with a probability level of 0.0014 (p <0.05). The benefit that can be learned from this research is the development of knowledge, especially in the paradigm of structural relationships of the role of competitive advantage in mediating market orientation, entrepreneurial orientation on marketing performance (a study on the processing and marketing of fishery products in Wakatobi Regency).